Children and young people's rights in the digital age: An emerging agenda. (May 2017) - Livingstone, Sonia; Third, Amanda
Rights-based approaches to children's digital media practices are gaining attention offering a framework for research, policy and initiatives that can balance children's need for protection online with their capacity to maximize the opportunities and benefits of connectivity. But what does it mean to bring the concepts of the digital, rights and the child into dialogue? Arguing that the child represents a limit case of adult normative discourses about both rights and digital media practices, this article harnesses the radical potential of the figure of the child to rethink (human and children's) rights in relation to the digital. In doing so, we critique the implicitly adult, seemingly invulnerable subject of rights common in research and advocacy about digital environments. We thereby introduce the articles selected for this special issue and the thinking that links them, in order to draw out the wider tensions and dilemmas driving the emerging agenda for children's rights in the digital age.